Herz & Gesundheit - Mühleisen L; Schlicht W (Dynamic Media Sales Verlag, 2018)
Background and Objectives: Due to innovative treatment methods and promising therapies in oncology, the number of cancer survivors has increased during recent years. The productivity and the ability to return to normal everyday life after recovery depend on the extent of the cancer-related chronic fatigue syndrome (CRF). The more severe the syndrome, the lower the physical and psychological performance of the patients. The purpose of this meta-analysis was to explore the effectiveness of guided physical activity to reduce CRF among adult, employed cancer survivors. Methods: Based on a systematic literature search, the statistical data from randomized-controlled trials published between 2007 and 2016 were integrated into a meta-analysis. The methodological quality of the selected trials was evaluated using the PEDro scale. The data were summarized by a meta-analytic statistic in the randomized effects model. Cohens d was calculated and the homogeneity and sensitivity were verified. The influences of moderating conditions were examined by regression analysis. Results: The eleven integrated studies revealed a significant however, heterogeneous global effect d =0.46 (95% CI: 0.16 0.77). The intervention length could explain the variance between the studies: The shorter the intervention, the stronger the effect. A publication bias could not be detected.Conclusion: The meta-analysis confirms the results from previously-published meta-analyses. Physical activity performed by cancer survivors can reduce CRF. The effectiveness ranges from low to moderate. However, the original studies are lacking methodological quality. The preferred outcome measures are self-report instruments prone to biases. KEY WORDS: Cancer Related Fatigue, Cancer Survivor, Physical Activity, Meta-Analysis